Kebijakan Biro Kemahasiswaan dalam Meningkatkan Kualitas Organisasi Intra di Kampus Stitnu Al Farabi Pangandaran - Azi Ramdani; Devi Silvia Dewi (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2025)
Students are an "elitist" component at the forefront of a nation in achieving progress in various fields of development. It cannot be denied that the history of nations in the world has never emphasized the role of students in building and maintaining human civilization (Mustika Cahyaning Pertiwi, et al, 2014: 229). As successors and holders of the baton of national leadership in the future and future managers of national development, students must prepare themselves as early as possible to carry out two large and heavy tasks at once, namely as pioneers of social change (agents of social change) and pioneers of community supervision (agents). of social control) by achieving the highest academic and non-academic achievements. Actively participating in student organizations on campus is an important and strategic alternative way for students to train and develop their full potential in scientific ways. This research was conducted using a qualitative research approach. Qualitative research is research aimed at describing and analyzing phenomena, events, activities, social, attitudes, beliefs, perceptions, thoughts of people individually and in groups.